Analysis of Business Communications and Entrepreneurs Services towards Online Shop Sales (Case Study on Doggy Medan Online Shop on Instagram) - Ferina Novelim; Victor Victor (Jurnal Mantik, 2022)
This study aims to determine the effect of communication and services on sales of Doggy_Medan. This type of research is explanatory research. The population in this study were all customer of Doggy_Medan which amounted to 152 customer. The sampling technique is to use a saturated sample where the entire population will be used as the research sample. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that communication and services partially or simultaneously have a positive and significant effect on sales of Doggy_Medan. Based on the results of this study, the implications for management are to further improve communication and services.